Circulating acetaminophen metabolites are toxicokinetic biomarkers of acute liver injury. Issue 4 (30th November 2016) - Vliegenthart, ADB; Kimmitt, RA; Seymour, JH; Homer, NZ; Clarke, JI; Eddleston, M; Gray, A; Wood, DM; Dargan, PI; Cooper, JG; Antoine, DJ; Webb, DJ; et al.
Abstract : Acetaminophen (paracetamol‐APAP) is the most common cause of drug‐induced liver injury in the Western world. Reactive metabolite production by cytochrome P450 enzymes (CYP‐metabolites) causes hepatotoxicity. We explored the toxicokinetics of human circulating APAP metabolites following overdose. Plasma from patients treated with acetylcysteine (NAC) for a single APAP overdose was analyzed from discovery ( n = 116) and validation ( n = 150) patient cohorts. In the discovery cohort, patients who developed acute liver injury (ALI) had higher CYP‐metabolites than those without ALI. Receiver operator curve (ROC) analysis demonstrated that at hospital presentation CYP‐metabolites were more sensitive/specific for ALI than alanine aminotransferase (ALT) activity and APAP concentration (optimal CYP‐metabolite receiver operating characteristic area under the curve (ROC‐AUC): 0.91 (95% confidence interval (CI) 0.83–0.98); ALT ROC‐AUC: 0.67 (0.50–0.84); APAP ROC‐AUC: 0.50 (0.33–0.67)). This enhanced sensitivity/specificity was replicated in the validation cohort. Circulating CYP‐metabolites stratify patients by risk of liver injury prior to starting NAC. With development, APAP metabolites have potential utility in stratified trials and for refinement of clinical decision‐making.